Development Of Integrated Science Teaching Materials Based On Problem Based Learning For Grade 8th Junior High School - fadila, tesya dwina; Yurnetti, Yurnetti (Universe, 2024)
The purpose of this study was to measure the validity and practicality of the Integrated Science learning module with the STEM-integrated Problem Based Learning model. This research was conducted at junior high school 1 Kota Solok in grade 8.H and grade 8. I. The type of research conducted is research and development (R&D). The research model used is the Plomp model. The plomp model consists of 3 stages, namely Preliminary research (initial investigation stage), Prototyping stage (prototype formation), and Assessment stage. The instrument used in this study is by using a questionnaire to test the validity and practicality. The validity test was carried out by an expert validator while the practical test was carried out by science teachers and eighth grade junior high school students. The results showed that the Validation Test obtained a validity value of 0.93 in the valid category. In the practicality test, the teacher achieved a practicality value of 0.89 in the practical category and the practicality test by students in the small group test achieved a practicality value of 0.89 in the practical category and the practicality test by students in the large group test (Field Test) the value achieved by practicality is 0.83 in the practical category. The results of the research carried out there are several suggestions where teachers and students can use these modules as additional teaching materials to support the learning process so that students play an active role in learning.